Flow diverter tail malapposition after implantation in the internal carotid artery for aneurysm treatment: a preliminary study - Wan, Zheng; Liu, Tianyi; Xu, Ning; Zhu, Wenhao; Qi, Yuan; Ma, Chunyang; Chen, Hao; Wang, Honglei (Frontiers in Neurology, 2023)
Background and purpose Favorable wall apposition of a flow diverter (FD) is essential for the treatment of intracranial aneurysms. The irretrievability and final drop point uncertainty of the proximal tail of the FD increase the difficulty of achieving good tail apposition. Therefore, understanding the factors associated with FD tail malapposition would be helpful for clinical practice. Methods A total of 153 patients with 161 FD deployments in the carotid artery between 2020 and 2023 were retrospectively collected from our center’s database for this study. Patient demographics, aneurysm characteristics, FDs, carotid artery anatomy, periprocedural complications, discharge modified Rankin scale (MRS) scores, and follow-up outcomes were investigated by comparing patients with and without FD tail malapposition. Comparisons were made with t tests or Kruskal–Wallis tests for continuous variables and the Pearson χ2 or Fisher exact test for categorical variables. Logistic regression was conducted to determine the predictors of malapposition. Results Tail malapposition occurred for 41 out of the 161 FDs (25.5%). Univariate analysis revealed that the FD brand, FD length, FD distal to proximal vessel diameter ratio, FD tail position (straight or curved), and curvature of the vessel curve were significantly associated with FD tail malapposition (p < 0.05). Further multivariate analysis demonstrated that the application of a surpass FD (p = 0.04), the FD distal to proximal vessel diameter ratio (p = 0.022), the FD tail position (straight or curved) (p < 0.001) and the curvature of the vessel curve (p < 0.001) were factors significantly associated with FD tail malapposition. No significant difference was found in periprocedural or follow-up outcomes. The classification of FD tail malapposition was determined from imaging. The two major patterns of FD tail malapposition are unattached tails and protrusive tails. Conclusion FD tail malapposition might be associated with a larger FD distal to the proximal vessel diameter difference, a curved vessel where the FD tail is located, and a larger curvature of the vessel curve. FD tail malapposition can be classified into unattached tails and protrusive tails, which have their own characteristics and should be noted in clinical practice.